“DYING A HUMAN THING” THE IMPORTANCE OF HUMANIZATION OF CURRENT MEDICINE - Oliveira, Jennifer Kelly Silva de; Paiva, Daniel Felipe Fernandes (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2020)
Objective: To report the experience of participating in the “Dying: a human thing” project from the perspective of the development of students in the health field. Methodology: The present work has a descriptive character of the experience report type, based on the experience of the extension project in focus, from its theoretical foundation to the development of the skills acquired during the execution from the perspective of an active participant. Results: The experience provided by the activity allows a comprehensive and very specific look at delicate topics in the medical routine, to foster the empathy of the participants and, therefore, assist in the support and complete care of patients who, inevitably, will experience moments losses in their lives, reaffirming the doctor's role not only as responsible for a singular patient, but also for the entire family structure that surrounds him. Conclusions: The project provides greater preparation for clinical practice, offering the expansion of the students' view of sensitive issues of loss to train sensitive and humanized professionals.